Mobile-based interventions in nursing education among undergraduate nursing students: An analysis - Zainudin, Airul Azizan; Mohd Mohadis, Hazwani; Ahmad, Norfadzilah (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
There is an enormous pressure for nursing education institution to become more dynamic to engage in fast-growing educational technology into the curriculum. This study discussed the literature on the implementation of mobile learning intervention in undergraduate nursing education mainly targeting learning outcomes and understanding the features and elements of mobile technology that lead to the success and failure of the interventions. Four main online databases searched; there were Ovid, Scopus, CINAHL and ProQuest. Citation tracking and scrutiny of reference lists were also undertaken in the search for additional papers. We included twelve papers reporting on mobile-based intervention with nursing learning activities. Seven out of twelve reported the employment of quasi-experimental pre-posttest, meanwhile four used randomized-controlled trial, and one experimental pre-posttest. Eight studies were from South Korea, two were from Taiwan, and one was from Finland and Brazil. Four implemented video-based, while the other three were virtual learning object, auditory-based content and communication-based intervention. Among the advantages of mobile technology addressed were easy access and promote learning feedback, which has subsequently resulted in improved retention of knowledge, skill performance, satisfaction and self-efficacy. Meanwhile, the disadvantages were lack of user satisfaction among video-based intervention studies and low skill practice score in auditory- and social network- based intervention studies. In summary, there were no single study claimed that their study as effective for clinical skill learning since the outcomes were unclear, but there is still room for improvement with better intervention design.